Islamic counting game: an interactive approach as a teaching and learning aid necessary in holistic education for digital society 5.0 / Zanirah Mustafa@Busu …[et al.]. - Mustafa @Busu, Zanirah; Mohamed, Abdul Majid Tahir; Awang@ Ab Rahman, Nurul Hidayah; Noor Zainan, Nurul Izzah; Junoh, Noraini; Mat Jusoh, Nor Asmira; lsmail, Mohd Khairul Anuar; Nik Din, Nik Muniyati; Yusuf, Norazmila (2021)
Accounting is one of the important knowledge of Islam. Many verses in the Quran and Hadith debate on accounting. It is a branch of social knowledge that records financial reports on all activities involving finance. Accounting reports are important for the benefits of the public as well as those who are involved in financial and accounting activities. Nonetheless, the calculation methods found in the Fundamental of Islamic Accounting course at UiTM are quite complicated with various concepts and formulas as practiced at various financial institutions. Therefore, this makes it difficult for students to understand and remember every available fonnula. Thus, students require new teaching and learning tools to facilitate their learning. Hence, teaching and learning aids are highlighted as one of the most recent transformations for computational learning in Islamic accounting.This im1ovative product is a teaching and learning tool for teaching and learning designed in the form of apps system in line with the needs of the education industry revolution 5.0. This im1ovative product contains a wide selection of training questions and formulas on the topic of calculating various types of zakat on the property (mal), insurance (takaful), charge (arrahnu) and various types of Islamic banking financing. The main objective of this paper was to evaluate the effectiveness of learning through the interactive application of Islamic counting games in the classroom. Literature search, documentation of observations, demographic and descriptive methods were also utilised through research surveys, observations and questionnaires on students. These methods were used to collect related data information. The findings reveal that the majority of the students did not know Islamic Counting Game. However, interestingly after the use of Islamic Counting Game in learning, most of them felt that Islamic Counting Game is very good and useful in their studies. Based on the findings, we can infer that the product is accepted and recognised by the students. Thus, it will benefit and impose significant impacts to the students and society as a whole.